2002
DOI: 10.1002/jsfa.1210
|View full text |Cite
|
Sign up to set email alerts
|

Varietal differences in terpene composition of blackcurrant (Ribes nigrum L) berries by solid phase microextraction/gas chromatography

Abstract: Relative amounts of volatile terpenes in berries of 10 different blackcurrant (Ribes nigrum L) cultivars were examined by solid phase microextraction/gas chromatography (SPME/GC). The optimisation of a variety of parameters affecting SPME enabled relative standard deviations from three replicates ranging from 2 to 12% to be achieved. Differences between cultivars in the proportions rather than in the qualitative composition of volatile terpenes were found, and the proportions of some terpenes were especially v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…Although the obtained results allowed to determine reliably the terpenic composition of Mentha piperita, two different SPME-fibres (65 m layer of PDMS/DVB and 85 m layer of polyacrylate) were additionally tested under the selected temperature and time conditions in order to evaluate their performance. The choice of the last two mentioned fibres was based on our previous experience in the extraction of terpenes from different matrices, other than plants [18,19] and on the theoretical adequacy of polyacrylate fibre for terpenic compounds, respectively. However, neither of these fibres provided higher peak areas than those obtained when PDMS was utilised.…”
Section: Resultsmentioning
confidence: 99%
“…Although the obtained results allowed to determine reliably the terpenic composition of Mentha piperita, two different SPME-fibres (65 m layer of PDMS/DVB and 85 m layer of polyacrylate) were additionally tested under the selected temperature and time conditions in order to evaluate their performance. The choice of the last two mentioned fibres was based on our previous experience in the extraction of terpenes from different matrices, other than plants [18,19] and on the theoretical adequacy of polyacrylate fibre for terpenic compounds, respectively. However, neither of these fibres provided higher peak areas than those obtained when PDMS was utilised.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, terpenoids originate from herbs or plants. For example, the unique intricate terpenic odour of blackcurrant berries was given oV from the terpene-containing glands in the plant (Ruiz del Castillo & Dobson, 2002). Mitiku, Ukeda, and Sawamura (2001) investigated the enantiomeric distribution in forty cold-pressed Citrus oil samples of -pinene, -pinene, sabinene and limonene, which are some of the same terpenoids found in our study, and reported that the species or varieties showed signiWcant diVerences in the enantiomeric purity of the terpenoids.…”
Section: Hydrocarbons and Carbonyl Compoundsmentioning
confidence: 95%
“…[22,36,38] This supports the known variability of the enantiomeric composition of monoterpenes in nature. [24,39] As observed in Table 3, the enantiomeric purity of (À)-DMHF, (À)-nerolidol and (+)-linalool in strawberries remained stable after pre-harvest treatments. From these results, it seems that natural hormonal compound treatments do not affect the enantioselective bioformation of (À)-DMHF, (À)-nerolidol and (+)-linalool during the ripening process.…”
Section: Effect Of the Pre-harvest Treatments On The Enantiomeric Purmentioning
confidence: 75%
“…However, the occurrence of pure (+)‐linalool in fruit aroma has previously been reported . This supports the known variability of the enantiomeric composition of monoterpenes in nature . As observed in Table , the enantiomeric purity of (−)‐DMHF, (−)‐nerolidol and (+)‐linalool in strawberries remained stable after pre‐harvest treatments.…”
Section: Resultsmentioning
confidence: 99%